Interaction of Question and Answer Method on Learning Interest of Grade IX Students of SMP Negeri 1 Pulau Rakyat Asahan - Marioga Pardede (Postgraduate, University of Mataram, 2024)
This study aims to determine the significant interaction of the question and answer method with the learning interests of class IX students of SMP Negeri 1 Pulau Rakyat Asahan. This type of research is correlational. The population in this study were class IX students of SMP Negeri 1 Pulau Rakyat Asahan consisting of 5 (five) classes, namely: IX-1, IX-2, IX-3, IX-4, and IX-5 as many as 185 people. The sample of this study was 50 people taken from class IX-1 students as many as 27 students and class IX-2 student’s as many as 23 students. The instruments used in this study were questionnaires, documentation and interviews. The questionnaire used as many as 30 questions with 5 (five) answer options. From the results of the study, it was concluded that there is a significant simultaneous relationship between the question and answer method and the learning interest of class IX students of SMP Negeri 1 Pulau Rakyat Asahan, this can be seen from the data showing r count (0.770) > r table (0.279) at a significance level of 5%, or can be formulated as 0.770 > 0.279. When viewed from the interpretation table